2015
DOI: 10.1021/acs.jpcc.5b01964
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistance of Manganese-Doped Colloidal Quantum Dot Films

Abstract: The magnetoresistance of films of manganese-doped colloidal quantum dots of CdSe, ZnO, HgS, and ZnTe is investigated. At low concentration of manganese ions (1% or less), the hyperfine splitting of the Mn 2+ electron spin resonance is resolved and similar to that of the bulk doped materials, indicating successful doping into the nanocrystals. At high Mn concentration (∼10%), the hyperfine splitting disappears because of interaction between the Mn 2+ ions. Thin films of Mn:CdSe, Mn:ZnO, and Mn:HgS quantum dots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…To ensure the completeness of the discussion on doping, although very few researchers have focused on the introduction of external impurities in the case of HgX NCs, it must be mentioned that Liu et al demonstrated Mn doping of HgS nanoparticles. 206 The authors introduced Mn (up to 15%) into the HgS matrix and observed an enhanced magnetoresistance with a higher Mn content. 197 .…”
Section: Dopingmentioning
confidence: 99%
“…To ensure the completeness of the discussion on doping, although very few researchers have focused on the introduction of external impurities in the case of HgX NCs, it must be mentioned that Liu et al demonstrated Mn doping of HgS nanoparticles. 206 The authors introduced Mn (up to 15%) into the HgS matrix and observed an enhanced magnetoresistance with a higher Mn content. 197 .…”
Section: Dopingmentioning
confidence: 99%
“…Colloidal semiconductor quantum dots (QDs) have huge potential as an attractive class of materials for future technological milestones in electronic, 1,2 optoelectronic, 3,4 magnetic, 5 and thermoelectric 6 devices because of their tunable electronic and optical properties at the nanoscale based on size, 7 shape, 8 and composition. 9 On the other hand, cost-effective solution-based methods are available for their synthesis, assembly, and processing into thin film devices.…”
Section: Introductionmentioning
confidence: 99%
“…Among existing synthetic methods for making Cd 1– x Mn x Se nanocrystals, diffusion doping has yielded simultaneously the largest Mn 2+ content and the greatest size uniformity, making NCs prepared by this method especially attractive for spectroscopic investigations and subsequent applications. Cd 1– x Mn x Se nanocrystals prepared by diffusion doping have now been used to demonstrate rich upper-excited-state magnetic circular dichroism (MCD), extraordinarily large excitonic Zeeman splittings, excitonic magnetic polarons, and enhanced positive magneto-resistance suggestive of electron magnetic polarons . Although the products of this chemistry are already proving useful, many details of the chemistry itself remain unexplored.…”
mentioning
confidence: 99%